Factors Influencing Recidivism in Offenders with Felony Charges on Life and Sex Offences (Indian Journal of Forensic Medicine & Toxicology, 2023)
Thailand is encountering higher recidivism rate, especially in felony cases. As recidivism is becoming a majorchallenge, factors influencing recidivism should be determined in order to develop policies on custody,rehabilitations and pre – release preparation. The purpose of this research is to study factors influencing recidivismin pre – release inmates on felony charges on life or sex offences. Random sampling method was used in the study.The participants consisted of 370 life and sex offenders on felony charges using Oxford Risk of Recidivism Tool(OxRec) as an assessment tool. The data was evaluated using multiple logistic regression analyses. The resultsshowed that factors significantly influencing recidivism are male, 12-24 month length of incarceration, previouscriminal history, employment and drug abuse.
Keywords: risk factors, recidivism, offenders, felony crimes